Influence of kenaf fibre in reinforced concrete beam with circular opening at midspan - Noor Aleeza Nadhirah, Abdillah (2018)
This thesis deals with experimental investigation on the performance of reinforced concrete beams with opening at mid-span added with kenaf fibres. Reinforced concrete beam with opening creates more cracking which also give rise to excessive deflection under service load. An attempt has been made to investigate the potential use of kenaf fibres can result in a significant reduction in conventional shear reinforcement and satisfied the requirement for strength and ductility by considering the concrete mix was based on the volume fraction of 0%, 1% and 2% of kenaf fibre content in concrete. Sodium hydroxide was used to treat kenaf fibres. Concrete compression and flexural tests were conducted for studying the compressive strength, load carrying capacity, ductility and energy absorption. Four beams experimental works were tested; one control reinforced concrete beam with no opening, one reinforced concrete beams with Vf=0% opening and two reinforced concrete beams with Vf=1% and Vf=2% opening respectively. All eighteen cubes specimen were tested until it failed in compression machine and found that the compressive strength deteriorated followed by the increasing of kenaf fibre in concrete. As for the beams, the maximum load carrying capacity decrease in fibre content